Non-fatal injuries among adults with activity limitations and participation restrictions. Issue 3 (2nd June 2005) - Xiang, H; Leff, M; Stallones, L
Abstract : Objective: To investigate non-fatal unintentional injuries among adults with activity/participation limitations. Design: Injuries in the previous 12 months were reported by a stratified probability sample of non-institutionalized adults. Based on self reported activity/participation limitations, 2602 respondents were classified into three groups (no limitations, moderate limitations, and severe limitations) and injury characteristics were compared. Results: A total of 19.2% of respondents reported activity/participation limitations. Twenty four percent (95% confidence intervals (CI) 14.5% to 33.6%) with severe and 17.8% (95% CI 13.2% to 22.4%) with moderate limitations were injured, compared with 12.6% (95% CI 10.6% to 14.7%) of respondents without limitations. The odds ratio of injury was 3.72 (95% CI 1.94 to 7.14) for respondents with severe and 1.87 (95% CI 1.25 to 2.77) for respondents with moderate limitations. The leading cause of injuries among respondents with activity/participation limitations was falls. Conclusions: Individuals with activity/participation limitations are at an increased risk for injuries.